Identifying volunteers’ motivation: a factor analysis study - Zainuddin, Norzairiah; Md Yusof, Zahayu; Zaini, Bahtiar Jamili; Mansor, Rosnalini (UPSI Press, 2020)
This paper focuses on the motivational factors that influence the volunteering acts of Universiti Utara Malaysia (UUM) students from the Foundation Management course by using factor analysis. The volunteering programme at the university are vastly expanded in the form of charity works, funding, sports activities, events, and other aspects by which the main and primary volunteers are students. This study was conducted to identify students’ volunteer motivation that complement the programme organiser goal and objectives. This is a quantitative research by using factor analysis method and questionnaire survey is conducted on the UUM students (n=204). In this study, only variables with factor loading of greater than 0.4 is included in the analysis. From extraction sums of squared loading, 5 factors with eigenvalues higher than one were extracted. The volunteer’s motivation of UUM students may be summarized in 5 factors which represents 61.49% of total variance explained. Research findings reveal only four main reasons that influenced students’ volunteer motivation. The main factor that influenced students’ volunteer motivations was self-enhancement. The other factors that follows were expression of values, career orientation, and interpersonal contacts. In the future, any volunteering programme that is planned needs to consider the students interests in order to fully maximize the students’ participation which concurrently would help the organiser to achieve the desired objective and outcome of the programme itself.